Penerapan Model Air Terjun pada Perancangan Panduan Wisata Kalimantan Tengah dengan Berbasis Android - Qamaruzzaman, M. Haris; Sam’ani (Jurnal Informatika, 2023)
The design stage is the most important part before an application is built. To help the public find out tourism information in Central Kalimantan, especially for those from outside the province, an information medium is needed in the form of a travel guide that can be used anywhere and anytime that can provide information about various kinds of information such as tourist objects, tourist facilities, etc. The design of this study used the System Development Life Cycle (SDLC) software development method with a waterfall model development approach. The results of this study are in the form of designing a system that will present Central Kalimantan travel guide information with a visual android-based waterfall modeling which will be used as the basis for building a tourist guide information system application.